Exploring Emotional Dissonance: On Doing What You Feel and Feeling What You Do - (:unkn) unknown (ELSEVIER SCIENCE BV, 2012)
The main purpose of this study is to investigate and to critically examine the link between emotional dissonance and employee well-being by drawing on a conceptualization of emotional dissonance through a theoretical model, focusing on the biggest retail store chains in Turkey. There is no such a study exploring the cognitive antecedents of customer contact service-workers' well-being like emotional dissonance in Turkey till now. Study results approve that emotional dissonance (surface acting) has a significant negative impact on employee well being (i.e. emotional exhaustion and job dissatisfaction) and the significant moderating impact of self concept (importance of authenticity and surface acting self efficacy) were also proven. Satisfaction of employees and maintaining their well being is an important intangible asset in creating a real competitive and strategic advantage therefore it has important contribution to strategic management process. Managerial implications and future research direction is also discussed in conclusion. (C) 2012 Published by Elsevier Ltd. Selection and/or peer-review under responsibility of the 8th International Strategic Management Conference
Keywords: Emotional dissonance; employee well-being; self concept; customer contact eervice workers; JOB-SATISFACTION; SERVICE; LABOR; SELF; BURNOUT; EXPRESSION; CONTAGION; SMILE